Q: What is 2x plus 9z plus 6x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

The above expression simplifies to 2x-y+9z

2x+92+6x

x + 2x + 6x = 9x

6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y

2x + 6x + 4x = 12x

5x + x - 6x + 2x = 2x

6x + 9 + 2x = 8x + 9

-2x + 11 + 6x = 4x + 11

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

6x

6X + 3 = 2X + 19Subtract 3 from each side:6X = 2X +16Subtract 2X:4X = 16Divide by 4X = 4

6x - 9 + 2x + 1 = 8x -8